Effects of pepper crop residues and inorganic fertilizers on soil properties relevant to carbon cycling and broccoli production. (2nd July 2013) - Moreno‐Cornejo, J.; Zornoza, R.; Faz, A.; Rosales, R. M.; Davidson, Donald
Abstract We conducted a two‐year experiment to evaluate the effects of fresh pepper residues (CR treatment) on soil properties and broccoli yield compared with the application of chemical fertilizers (CF treatment). Soil‐state 13C nuclear magnetic resonance (13C NMR) spectroscopy was used to characterize the organic composition of added residues and surface soil. We also measured total and soluble organic carbon and different biochemical properties associated with the C cycle. The results show that large application rates of CR increased microbial biomass carbon (MBC) and arylesterase and β‐glucosidase activities compared with the control. There was a significant increase in MBC for the CF treatment only with the greatest application rate. No differences in soil organic carbon composition and structure were found between treatments with soil organic C, soluble C, basal soil respiration, arylesterase and β‐glucosidase activities correlated positively with the soil carboxylic region and negatively with the aromatic region of the spectra. Broccoli yield was significantly more for the second crop cycle with maximum values for the greatest application rates of CF and CR indicating that crop residues with a minimum amount of chemical fertilizers can be used to obtain an adequate yield. The use of pepper residues as an organic amendment improved biochemical properties of the soil with positive effects on broccoli quality and had no negative impact on yield.